Feasibility of LTE 700 MHz Digital Dividend for Broadband Development Acceleration in Rural Areas - Denny Setiawan; Djamhari Sirat; Dadang Gunawan (LPPM ITB, 2012)
The need of broadband services to reduce digital divide in rural areas had increased in the recent years. The government of the Republic Indonesia shared similar intention and had set guidance of ICT development in its